FREQUENCY CHARACTERISTICS OF THE GENES OF THE SECOND PHASE OF DETOXIFICATION OF XENOBIOTICS IN WOMEN OF rUSSIAN AND BURYAT ETHNIC GROUPS - E. E. Stupko (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The article presents the results of the analysis of the distribution of genotypes and alleles of polymorphic loci gene GSTP1 (*A, *B, *C, *D), GSTT1 (del) and GSTM1 (del) in 28 women Russian and 30 women of Buryat ethnic groups. As a result, the work showed a statistically significant difference in genotype AC gene GSTP1 among the study groups. As carriers of other genotypes of genes GSTP1, GSTT1, and GSTM1 showed no significant difference